2021
DOI: 10.1177/1120672121996638
|View full text |Cite
|
Sign up to set email alerts
|

Bruch’s membrane opening-minimum rim width: An alternative OCT biomarker study for multiple sclerosis

Abstract: Purpose: Bruch’s membrane opening-minimum rim width (BMO-MRW) and RNFL measured using anatomic positioning system (APS-RNFL) are novel OCT methods and remained unexplored in MS patients. To investigate the novel parameters of spectral-domain OCT as an alternative biomarker in patients with multiple sclerosis (MS). Methods: Retrospective cohort study; participants consisted of relapsing-remitting MS (RRMS) patients and healthy controls (HC). Eyes were classified according to the presence of MS and previous opti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
3
0
2
Order By: Relevance
“…Other, more unusual parameters, such as the thickness of lamina cribrosa and the Bruch’s membrane opening-minimum rim width, are of no utility for discriminating between patients with and without a history of ON [ 23 , 24 ].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Other, more unusual parameters, such as the thickness of lamina cribrosa and the Bruch’s membrane opening-minimum rim width, are of no utility for discriminating between patients with and without a history of ON [ 23 , 24 ].…”
Section: Optical Coherence Tomographymentioning
confidence: 99%
“…Die einfache Optikusatrophie anderer Genese zeigt die Verdünnung der BMO-MRW in viel geringerem Maße als bei den Glaukomen. Bei MS fanden Nguyen et al [5] mit BMO-MRW nur eine grenzwertige Korrelation mit der Kontrastempfindlichkeit und Özbilen et al [6] befanden BMO-MRW als für MS unspezifischen Biomarker. Jonas et al [7] beschrieben bei der einfachen Optikusatrophie nur eine geringgradig vergrößerte Exkavation, ophthalmoskopisch zeigt sich die Papille blass und im Niveau flacher als vitale Papillen.…”
Section: Schichtdickenverlust Bmo-mrwunclassified
“…Simple optical nerve atrophy from other causes is characterized by a much lower level of BMO-MRW thinning than is the case in glaucomas. In MS cases, Nguyen et al [5] determined only a marginal correlation between BMO-MRW and contrast sensitivity and Özbilen et al [6] found BMO-MRW to be a non-specific biomarker for MS. In cases of simple optic nerve atrophy, Jonas [7] described only slightly enlarged excavation and ophthalmoscopy shows pallid papillae with a flatter level than vital papillae.…”
Section: Loss Of Bmo-mrw Layer Thicknessmentioning
confidence: 99%
See 1 more Smart Citation
“…Many diseases can damage this neural pathway, leading to retinal nerve fiber layer defect (RNFLD). RNFLD can be found in eyes with ischemic optic neuropathy, glaucomatous optic neuropathy, optic disc drusen, retinitis pigmentosa, retinal artery occlusion, contusion of the optic nerve, compression of pituitary tumor, visual pathway impairment, toxic optic neuropathy, and as a sequela of long-standing papilledema, optic neuritis, etc [1][2][3][4][5][6][7][8] . In addition, many risk factors, such as age, race, gender, blood pressure, blood glucose, smoke, etc., are known to increase an individual's chance of developing RNFLD [9][10][11] .…”
Section: Introductionmentioning
confidence: 99%